Answer:
A) y = -(8/3)m - 2
B) y = 4x - 1
C) y = -3.2x - 4
D) y = -2.5x - 3
Explanation:
A) In the first equation, when x = 0, y = -2
From y = mx + c, we can say that
-2 = 0 + c
c = -2
Also,when y = 0, x = -0.75
Thus, 0 = -0.75m - 2
m = -2/0.75 = -8/3
Thus, y = -(8/3)m - 2
B) when x = 0, y = -1
From y = mx + c, we can say that
-1 = 0 + c
c = -1
Also,when y = 0, x = 0.5
Thus, 0 = 0.5m - 2
m = 2/0.5 = 4
y = 4x - 1
C)when x = 0, y = -4
From -4 = mx + c, we can say that
-4 = 0 + c
c = -4
Also,when y = 0, x = -1.25
Thus, 0 = -1.25m - 4
m = - 4/1.25 = -3.2
y = -3.2x - 4
D) when x = 0, y = -3
From y = mx + c, we can say that
-3 = 0 + c
c = -3
Also,when y = 0, x = -1.2
Thus, 0 = -1.2m - 3
m = -3/1.2 = -2.5
y = -2.5x - 3